BIOACTIVITY STUDIES ON LANTANA CAMARA LINN. - M. REMYA; NIMHOR VASHUM; SUBHA SIVASANKAR (International Journal of Pharma and Bio Sciences, 2013)
Diphenyl-2-picryl-hydrazyl (DPPH) radical, reducing power and Nitric oxide radical scavenging assays were carried out to evaluate the antioxidant potential of the Methanol, Chloroform, Hot water and Diethyl ether extracts of the roots of Lantana camara. The methanolic extract of the roots of L.camara was found to be the most effective. The total phenolic content of the roots were 39.32µg pyrocatechol equivalents of phenols respectively. GC-MS analysis of the methanolic extracts from roots revealed the presence of β-caryophyllene (21.22%), Limonene (13.27%), Isocaryophyllene (12.73%), oleanolic acid (9.98%) γ-terpinene (8.38%) and α-humulene (8.17%) as the main components. The results of the present study give credence to the innumerable therapeutic claims of the plant in the traditional system. Antibacterial activity was tested against four different bacteria using agar well diffusion method. Zones of inhibition were measured with the different concentrations of the root extracts. Methanol extract was effective against all the bacteria tested.